Quantitative relations between exposure to respirable quartz and risk of silicosis. Issue 3 (1st March 2003) - Buchanan, D; Miller, B G; Soutar, C A
Abstract : Aims: To reanalyse exposure-response data from a Scottish colliery to gain a more detailed knowledge of the relations between exposure to quartz and risks of silicosis in coal miners, and hence inform the debate on an appropriate occupational standard for respirable quartz. Methods: Detailed data on working times at different quartz concentrations were combined to produce exposure profiles for miners who had provided a full chest radiograph at a follow up survey. Logistic regression methods were used to model profusion of radiographic abnormalities category 2/1+, and a general exposure index was used to compare different quartz exposure measures in these models. Results: Results in 371 men aged 50–74 indicated that cumulative quartz exposure at higher concentrations resulted in proportionally greater risks of abnormalities. One g.h.m −3 of cumulative exposure at quartz concentrations greater than 2 mg.m −3 was estimated to have equivalent risks to 3 g.h.m −3 at lower concentrations. The timing of exposure relative to follow up appeared less important, although the study had limited power to compare different lag periods between exposure and effect. Conclusions: Quantification of the risks of silicosis should take account of variations in quartz exposure intensity, particularly for exposure to concentrations of greater than 1 or 2 mg.m −3, even if exposure is for relatively short periods. The risks of silicosis over a working lifetime can rise dramatically with even brief exposure to such high quartz concentrations. Risk estimates are given, to inform choice of control limits.